MODEL OF PHYSICAL HAZARD RISK IN UNIVERSITY LOCATED IN FACTORY AREA - Rizkiyah Nur Putri; M. Trifiananto (Universitas Darussalam Gontor, 2019)
Corporate-based universities are being established by the Ministry of Higher Education and one of them is the Semen Indonesia Gresik of Community Collage (AKSI Gresik). The location that is integrated with the cement factory in Gresik city supported by adequate facilities is one of its advantages. However, the health hazards that exist at the factory location also pose a threat to universities, one of which is the danger of physics. The purpose of this study is to produce information from smart tools that make it easier for the academic community to identify potential health problems and provide input / recommendations for hazard control of physical hazard conditions including climate hazards, noise, vibration, microwaves, lighting and magnetic fields. Hazard control includes substitution / elimination of hazards, input from engineering, administration and proper use of PPE. The method used is quantitative by taking measurements in March - April 2019 in the rector's building, lecture building, machine worshop and heavy equipment workshop. The measurement results will be entered into the manufacture of smart tools by using the Java program (NetBeans IDE 18.1. This research produces applications that can be operated on personal computers that indicate the potential danger of noise, vibration for workshops and lighting hazards for the room. Health problems that could potentially be suffered in the form of hearing disturbances, tremors of the limbs and eye fatigue resulting in minus eyes.The output from the design of smart tools provides the conclusion that proper hazard control in the AKSI Gresik is engineering, namely the presence of noise dampers and vibration absorbers and the use of PPE such as ear plugs / ear muffs and the use of vibration dampening gloves is the solution.Keyword: danger of physics, hazard control of physical hazard conditions, smart tools